THE ROLE COMMUNITIES IN THE NATIONAL PROGRAM FOR COMMUMITY EMPOWERMENT (PNPM-M) IN DISTRICT KINALI WEST PASAMAN - WILMAWITA, WILMAWITA; Drs. Dasrizal, MP, Drs. Dasrizal, MP; Prari Keslan, Widya (Pendidikan Geografi, 2014)
ABSTRACT The study aims to look at the role of communities in the National Program for Community Empowerment (PNPM-M) in District Kinali West Pasaman. The problem  often arises  about peoples behavior, community participation and education level. Methods of study is a descriptive, solving  method problems investigated by describing and implementing based on the facts that appear or as they are. The location of this research is in the District of West Pasaman Kinali. Sampling was done with a proportional random sampling technique with the proportion of 25%  to 88 of the 369 respondents. Data were collected through observation and questionnaire data analysis techniques using a percentage formula, namely to the role of the community in PNPM-Mandiri. The results of  study indicate that: 1) The behavior of people in the PNPM-Mandiri is generally already comply with the regulations given by the Implementation Unit (CGU) with a percentage of 95.45%. 2) participation in PNPM-Mandiri is less participate with the percentage of 13.64%, this is due to the general public only occasionally and rarely participate in meetings of mutual cooperation. 3) the level of public  education with  percentage of 45.45%, this is due to the general public primary school and only partially graduate PT.